Perbedaan tingkat depresi pada wanita menopause yang tidak bekerja dan bekerja di Dusun Tegalsari Desa Jabon Kecamatan Mojoanyar Kabupaten Mojokerto - Dwi w, Binarti; Mardanik, (JURNAL KEPERAWATAN SEHAT, 2013)
ABSTRACTDeep sadness which is caused by psychological or physical changes at menopause can cause depression. This condition is experienced by both housewives and working mothers. The research objective is to determine differences in depression level in menopausal women who not worked and worked in Tegalsari Jabon Village Mojoanyar District Mojokerto. Research design is analytical comparative with cross sectional approach. Population is all menopause women as much as 69 people. Samples were taken using total sampling to obtain 67 respondents, because two people were not willing to become respondents. The independent variable is working status of women and dependent variable is level of depression in menopause women. Data was collected using the Geriatric Depression Scale (GDS-15) which has been modified, then analyzed using cross tabulation. Result shows respondents who worked, mostly (32.1%) not in depressed disorder (normal), because the psychosocial stressors could be overcome due to the maturity of age, good social status, and high level of education. Respondents who did not work, majority (38.5%) had moderate depression and (30.7%) experienced severe depression, caused by lack of ability in dealing with psychosocial stressors due to reduced in intensity of daily work, low social status and educational level. So there are differences in depression level in menopause women who not worked and worked. Respondents are expected to increase their knowledge of menopause, especially from health professionals. Family should take their family member with severe depression to health service for further diagnosis and how to handle this problem. Health workers are expected to provide health education about menopause through various activities, such as Posyandu Lansia and other social gatherings.Keywords: depression level, working status, menopause women